THE CONTEMPORARY SIGNIFICANCE OF IBN SINA’S ETHICAL VIEWS - Uralov Dilshodbek (Western European Studies, 2026)
This article analyzes the ethical views of the great thinker Abu Ali Ibn Sina and reveals their significance for modern society, personal development, and social relations. Ibn Sina’s ethical ideas are examined in close connection with his philosophical, medical, and pedagogical teachings
Keywords: Ibn Sina; ethics; virtue